Relationship between body weight and linear body dimensions of Guinea pig (Cavia porcellus) in the southern guinea savannah zone of Nigeria - Sunday Acheneje, Egena Stephen (Malaysian Journal of Science, 2010)
Data on 24 weaned guinea pigs were used to evaluate the relationship between live body weights and linear measurements. The traits measured were body weight (BW), body length (BL), heart girth (HG), trunk length (TL), fore leg length (FLL), hind leg length (HLL) and ear length (EL). Measurements of body components were regressed against live weight at 4, 6, 8, 10 and 12 weeks using linear, quadratic and exponential regression analyses. The regression equations, estimates of parameters and coefficient of determination (R2 ) for the fitted functions were determined. Strong interrelationships (p<0.05) were observed among the parameters. The coefficient of determination (R2 ) values varied from 0.00 to 0.42%, 0.16 to 0.78%, 0.10 to 0.81%, 0.15 to 0.80% and 0.03 to 0.68% at 4, 6, 8, 10 and 12 weeks respectively. Body length (BL) had higher R2 value at 4 weeks (0.42%), 6 weeks (0.78%) and 8 weeks (0.81%) respectively with the exponential function while; heart girth had higher R2 value at 10 weeks with the exponential function (0.80%) and at 12 weeks (0.68%) with quadratic function. Based on R2 value, exponential function was generally superior in terms of goodness of fit to the data and its ability to predict body weight. (Keywords: Body length, heart girth, trunk length, fore leg length, hind leg length, ear length)